PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN PENGELOLAAN SDM TERHADAP KINERJA PERSONEL YANG DIMEDIASI OLEH DISIPLIN KERJA PADA BIRO SDM POLDA NTB - Prabowo, Toni (MAP (Jurnal Manajemen dan Administrasi Publik), 2025)
The purpose of the study was to analyze the Influence of Transformational Leadership and Human Resources Management on Personnel Performance Mediated by Work Discipline at the NTB Police Human Resources Bureau. The type of research is explanatory with a quantitative approach. The research sample was 53 respondents and analyzed with SEM-PLS. The results of the study show that personnel performance is included in the very good category, transformational leadership is included in the very good category, human resource management is included in the very good category, and work discipline is included in the very good category, transformational leadership has a direct and significant effect on work discipline. Human resource management has a direct and significant effect on work discipline. Transformational leadership has a direct and significant effect on personnel performance. Human resource management has a direct and significant effect on personnel performance. Work discipline has a direct and significant effect on personnel performance. Transformational leadership has an indirect and significant effect on personnel performance mediated by work discipline. Human resource management has an indirect and significant effect on personnel performance mediated by work discipline.